2020
DOI: 10.31729/jnma.5271
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Misuse of Topical Corticosteroid among Dermatology Outpatients

Abstract: Introduction: Topical corticosteroids misuse has become one of the burning issues in many countries across the globe. They are known to cause a myriad of adverse effects which include local effects commonly and systemic effects rarely. In dermatology practice, one of the common problems we see these days are steroid-induced and steroid aggravated dermatoses. So, this study was done to find the prevalence of misuse of topical corticosteroid among dermatology outpatients. Methods: A descriptive cross-secti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
9
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 19 publications
0
9
0
1
Order By: Relevance
“…The geographical area where the study was conducted experiences tropical weather, which favors dermato-phytic growth. Rampant use of over the counter topical corticosteroids is common in Nepal[ 6 ] which has further increased the problem of tinea. Dermato-phytic infections favor the summer months due to increased heat and humidity.…”
Section: Discussionmentioning
confidence: 99%
“…The geographical area where the study was conducted experiences tropical weather, which favors dermato-phytic growth. Rampant use of over the counter topical corticosteroids is common in Nepal[ 6 ] which has further increased the problem of tinea. Dermato-phytic infections favor the summer months due to increased heat and humidity.…”
Section: Discussionmentioning
confidence: 99%
“…A brief literature search revealed that TCs are more commonly misused for dermatophyte infections. A study by Shrestha et al 10 analysed that the TCs are more commonly misused for dermatophytosis. Jhaj et al 11 concluded that most of the steroid preparations had been bought without a prescription for the treatment of dermatophytosis.…”
Section: Introductionmentioning
confidence: 99%
“…Srivastava 14 also concluded that the primary dermatosis for which TCs misused was dermatophytosis. Initially, these TCs suppress the normal cutaneous immune responses to dermatophytes resulting in ineffective elimination of dermatophytes culminating in chronic, widespread infection and allowing the fungus to grow easily 10 . As the inflammation is suppressed, the fungal infection becomes less visible, and the associated symptoms are reduced.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies (15,29,30) have also focused on the inappropriate use of systemic glucocorticoids in primary care institutions. Other studies have described prescribing patterns of topical glucocorticoids (31)(32)(33)(34)(35), and factors associated with their inappropriate use (36-39). However, few studies have comprehensively examined the prescription patterns and factors associated with inappropriate use of systemic glucocorticoid in primary care institutions.…”
Section: Introductionmentioning
confidence: 99%